Anatomical Variations of the Vertebral Artery in the Upper Cervical Spine: Clinical Relevance for Procedures Targeting the C1/C2 and C2/C3 Joints. Issue 4 (1st May 2018) - Elgueta, Maria Francisca; Ortiz Jimenez, Johanna; Wang, Nina Nan; Pérez Lara, Almudena; Chankowsky, Jeffrey; Charghi, Roshanak; Tran, De Q.; Finlayson, Roderick J.
Abstract : Background and Objectives: Accidental breach of the vertebral artery (VA) during the performance of cervical pain blocks can result in significant morbidity. Whereas anatomical variations have been described for the foraminal (V2) segment of the VA, those involving its V3 portion (between the C2 transverse process and dura) have not been investigated and may be of importance for procedures targeting the third occipital nerve or the lateral atlantoaxial joint. Methods: Five hundred computed tomography angiograms of the neck performed in patients older than 50 years for the management of cerebrovascular accident or cervical trauma (between January 2010 and May 2016) were retrospectively and independently reviewed by 2 neuroradiologists. Courses of the VA in relation to the lateral aspect of the C2/C3 joint and the posterior surface of the C1/C2 joint were examined. For the latter, any medial encroachment of the VA (or one of its branches) was noted. The presence of a VA loop between C1 and C2 and its distance from the upper border of the superior articular process (SAP) of C3 were also recorded. If the VA loop coursed posteriorly, its position in relation to 6 fields found on the lateral aspects of the articular pillars of C2 and C3 was tabulated. Results: At the C1/C2 level, the VA coursed medially over the lateral quarter of the dorsal joint surface in 1% of subjects (0.6% and 0.4% on the left and right sides, respectively; P = 0.998). A VA loop originating between C1 and C2 was found to travel posteroinferiorly over the anterolateral aspect of the inferior articular pillar of C2 in 55.5% of patients on the left and 41.9% on the right side ( P < 0.001), as well as over the SAP of C3 in 0.4% of subjects. When present in the quadrant immediately cephalad to the C3 SAP, VA loops coursed within 2.0 ± 1.5 and 3.3 ± 2.5 mm on the left and right sides, respectively, of its superior aspect ( P < 0.001). Conclusions: The VA commonly travels adjacent to areas targeted by third occipital nerve procedures and more rarely over the access point for lateral atlantoaxial joint injections. Modifications to existing techniques may reduce the risk of accidental VA breach.